Countering the Global : Anti-Global Religion, Global Dissent and Multiple Globalisms - Andersen, Peter B.,; Hvithamar, Annika,; Jacobsen, Brian Arly,; Warmind, Morten, (International Studies in Religion and Society ;, 2025)
Most great religious traditions are global in scope, but they are often used to promote nationalist and isolationist ideas. Why do politicians in Poland and Lithuania stress the strong bond between the Catholic Church and the national identities? And how are ethno-religious conflicts expressed in Norway? In this book, you will find new data and new insights, providing explanations for these and other questions. Fascinating case studies from Europe and China are the basis for analyses on how global interconnectedness sparks both unity and conflict within religious spheres, demonstrating the interplay of local and global influences as well as the dynamics of glocalization. Contributors are: Milda Ališauskienė, Peter B. Andersen, Eileen Barker, Peter Beyer, Irena Borowik, Lisbet Christoffersen, Inger Furseth, Peter Gundelach, Annika Hvithamar, Massimo Introvigne, Hans Raun Iversen, Brian Arly Jacobsen, Niels Kærgaard, Pål Repstad, and Morten Warmind. Brill publications by Margit Warburg Books Citizens of the World. A History and Sociology of the Baha'is from a Globalisation Perspective (2006). ISBN 978 90 04 14373 9 (Hardback) / 978 90 47 40746 1 (E-Book). Published as Volume 106 in Numen Book Series Holy Nations and Global Identities. Civil Religion, Nationalism, and Globalisation (2009) (Edited with Annika Hvithamar & Brian Jacobsen). ISBN 978 90 04 17828 1 (Hardback) / 978 90 47 44063 5 (E-Book). Published as Volume 10 in International Studies in Religion and Society Book chapters & journal articles "Globalization, Migration and the Two Types of Religious Boundary: A European Perspective." In: Peter Beyer & Lori Beaman (Eds.), Religion, Globalization and Culture (2007), pp. 79-99. ISBN 978 90 04 15407 0 (Paperback) / 978 90 47 42271 6 (E-Book). Published as Volume 6 in International Studies in Religion and Society . Chapter DOI: https://doi.org/10.1163/ej.9789004154070.i-608.34 "Introducing Civil Religion, Nationalism and Globalisation." (With Annika Hvithamar) In: Annika Hvithamar, Brian Jacobsen & Margit Warburg (Eds.), Holy Nations and Global Identities. Civil Religion, Nationalism, and Globalisation (2009), pp. 1-17. ISBN 978 90 04 17828 1 (Hardback) / 978 90 47 44063 5 (E-Book). Published as Volume 10 in International Studies in Religion and Society . Chapter DOI: https://doi.org/10.1163/ej.9789004178281.i-310.3 "Transnational Civil Religion: The Fourth of July in Denmark." In: Annika Hvithamar, Brian Jacobsen & Margit Warburg (Eds.), Holy Nations and Global Identities. Civil Religion, Nationalism, and Globalisation (2009), pp. 271-293. ISBN 978 90 04 17828 1 (Hardback) / 978 90 47 44063 5 (E-Book). Published as Volume 10 in International Studies in Religion and Society . Chapter DOI: https://doi.org/10.1163/ej.9789004178281.i-310.106 "Baha'is of Iran: Power, Prejudices and Persecutions." In: Anh Nga Longva & Anne Sofie Roald (Eds.), Religious Minorities in the Middle East. Domination, Self-Empowerment, Accommodation (2012), pp. 195-218. ISBN 978 90 04 20742 4 (Hardback) / 978 90 04 29044 0 (Paperback) / 978 90 04 21684 6 (E-Book). Published as Volume 108 in Social, Economic and Political Studies of the Middle East and Asia . Chapter DOI: https://doi.org/10.1163/9789004216846_010 "The Baha'is of the North." In: James R. Lewis & Inga Bårdsen Tøllefsen (Eds.), Handbook of Nordic New Religions (2015), pp. 77-92. ISBN 978 90 04 29244 4 (Hardback) / 978 90 04 29246 8 (E-Book). Published as Volume 11 in Brill Handbooks on Contemporary Religion . Chapter DOI: https://doi.org/10.1163/9789004292468_006 "By Grace: Recognition of Religious Minority Associations in Denmark from the Reformation until 2018." In: Journal of Religion in Europe 12(4): 353-383 (2019). DOI: https://doi.org/10.1163/18748929-01204001 "Pros and Cons in Multidisciplinary Research on Religion." In: Martha Middlemiss Lé Mon & Anna-Sara Lind (Eds.), Doing Multidisciplinary Research on Religion: Methodological, Conceptual and Theoretical Challenges (2024), pp. 84-101. ISBN 978 90 04 67780 7 (Hardback) / 978 90 04 67779 1 (E-Book). Published as Volume 36 in International Studies in Religion and Society . Chapter DOI: https://doi.org/10.1163/9789004677791_008